Smart Rural Development: Using Information Technology for Sustainable Rural Planning - Fayaz Gul Mazloum Yar; Mohammad Edris Naderi (Eduvest - Journal of Universal Studies, 2025)
Sustainable rural development is essential for enhancing rural communities' economic, social, and environmental well-being. However, challenges such as inadequate infrastructure, limited access to essential services, and environmental degradation hinder progress in this domain. Information and Communication Technologies (ICT) offer innovative solutions to overcome these obstacles by facilitating better planning, improved decision-making, and enhanced connectivity. This study explores the role of ICT in sustainable rural development, emphasizing its application in agriculture, healthcare, education, and governance. Through Geographic Information Systems (GIS), remote sensing, mobile technologies, and e-governance platforms, ICT fosters efficient resource management, boosts economic resilience, and strengthens community participation. Despite the potential benefits, digital literacy gaps, infrastructure deficiencies, and financial constraints remain key barriers to implementation. The study highlights the importance of strategic investments, stakeholder collaboration, and policy interventions to maximize ICT’s impact on rural development. By integrating ICT into planning frameworks, rural communities can achieve long-term sustainability, economic growth, and improved quality of life